1987
DOI: 10.1007/bf02455993
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine pharmacokinetics in continuous ambulatory peritoneal dialysis

Abstract: Ranitidine kinetics in renal failure were evaluated in six patients undergoing continuous ambulatory peritoneal dialysis (CAPD). On separate occasions each patient received either 50 mg intravenously (i.v.) or 150 mg orally of ranitidine HCl. Following i.v. administration, the plasma concentration vs time curve was best described by a two compartment model with firstorder elimination. The mean +/- SD distribution and elimination rate constants were 2.47 +/- 0.78 and 0.098 +/- 0.013 h, respectively. The area un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…F (54.3 ± 13.5%) is comparable with that found in normal individuals (52%) [Comstock et al 1989;Garg et al 1983;Sica et al 1987). Cmax is delayed in patients with renal impairment compared with that in individuals with normal renal function (3 to 4h vs 2h) [McGonigle et al 1982a;Sica et al 1985b].…”
Section: In Renal Insufficiencysupporting
confidence: 74%
See 2 more Smart Citations
“…F (54.3 ± 13.5%) is comparable with that found in normal individuals (52%) [Comstock et al 1989;Garg et al 1983;Sica et al 1987). Cmax is delayed in patients with renal impairment compared with that in individuals with normal renal function (3 to 4h vs 2h) [McGonigle et al 1982a;Sica et al 1985b].…”
Section: In Renal Insufficiencysupporting
confidence: 74%
“…During a single haemodialysis session of 4 to 6h the serum ranitidine concentrations decreased by 60% after intravenous administration and by 55% after oral administration (Comstock et al 1989;McGonigle et al 1982a,b). The quantity of drug removed represented less than 10% of the administered dose (Comstock et al 1988(Comstock et al , 1989Garg et al 1985;Sica et al 1985a). During haemofiltration, Gladziwa et al (1988b) found that 17.1 ± 6.3% of the administered dose was removed, whereas Pollock et al (1986) found only a 2.1 ± 1.4% removal.…”
Section: In Renal Insufficiencymentioning
confidence: 93%
See 1 more Smart Citation
“…Based on the extent of extra- corporeal clearance cimetidine has been categorised as a slightly dialysable (5 to 20%) drug (Knoben & Anderson, 1983). A recent report on the peritoneal clearance of ranitidine revealed that only 1.3 and 0.9% of the administered dose was removed by CAPD over a period of 20 h following intravenous and oral routes, respectively (Sica et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Sica et al [20] analyzed the pharmacokinetics of H2B using ranitidine and reported that H2B clearance was decreased in continuous ambulatory PD patients compared to that observed in individuals with normal kidney function. Therefore, acid suppression with H2B treatment may be more powerful than that obtained with PPIs in PD patients.…”
Section: Discussionmentioning
confidence: 99%